Orthopedic surgeons' and neurologists' attitudes towards second opinions in the Israeli healthcare system: a qualitative study - Greenfield Geva; Pliskin Joseph S; Wientroub Shlomo; Davidovitch Nadav (BMC, 2012)
Abstract Background Second opinion is a treatment ratification tool that may critically influence diagnosis, treatment, and prognosis. Second opinions constitute one of the largest expenditures of the supplementary health insurance programs provided by the Israeli health funds. The scarcity of data on physicians' attitudes toward second opinion motivated this study to explore those attitudes within the Israeli healthcare system. Methods We interviewed 35 orthopedic surgeons and neurologists in Israel and qualitatively analyzed the data using the Grounded Theory approach. Results As a common tool, second opinion reflects the broader context of the Israeli healthcare system, specifically tensions associated with health inequalities. We identified four issues: (1) inequalities between central and peripheral regions of Israel; (2) inequalities between private and public settings; (3) implementation gap between the right to a second opinion and whether it is covered by the National Health Insurance Law; and (4) tension between the authorities of physicians and religious leaders. The physicians mentioned that better mechanisms should be implemented for guiding patients to an appropriate consultant for a second opinion and for making an informed choice between the two opinions. Conclusions While all the physicians agreed on the importance of the second opinion as a tool, they raised concerns about the way it is provided and utilized. To be optimally implemented, second opinion should be institutionalized and regulated. The National Health Insurance Law should strive to provide the mechanisms to access second opinion as stipulated in the Patient's Rights Law. Further studies are needed to assess the patients' perspectives.